RI 7834 Low-Temperature Heat Capacity And High-Temperature Enthalpy Of Tial3 - J. M. Stuve (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Thermodynamic properties were determined by the Bureau of Mines for the intermetallic compound, TiA13. Heat capacities were obtained from 5 to 303 K by adiabatic calorimetry. The derived value of S2 1s is 22.08±0.07 cal/deg¬mole. Enthalpies relative to 298 K were obtained from 298 to 1,413 K by copper-block drop calorimetry. No anomalous thermal behavior was noted in the temperature ranges investigated. Low- and high-temperature data were combined with a known enthalpy of formation at 298 K to give values of enthalpy of formation and Gibbs energy formation, 0 to 1,400 K.